Abstract ID: 126 Evaluation of the clinical translation of an optimized Compton camera during Boron Neutron Capture Therapy for melanoma patients. (October 2017) - Gong, Chunhui; Tang, Xiaobin; Shu, Diyun; Shao, Wencheng; Geng, Changran
Abstract : Introduction: Boron Neutron Capture Therapy (BNCT) [1] is a binary radiotherapy based on 10 B(n, α 7 Li reaction, whose clinical outcome depends on the deposited dose, associated with both the thermal neutron flux and the boron concentration distribution. However, it's still an on-going challenge to verify the boron concentration in real time. Potentially, one can measure the 0.478-MeV prompt gamma rays de-excited from 7 Li * to monitor the boron concentration in vivo. Based on our previously optimized Compton camera (CC)[2], which has higher efficiency than collimator based SPECT techniques[1], this study focuses on the evaluation of the clinical translation of the CC for Melanoma patients. Materials and Methods: A virtual patient with one melanoma lesion was constructed and irradiated with epithermal neutron beam; the boron concentration was set as from 30 to 100 ppm. The List-Mode Maximum Likelihood Expectation Maximization (LM-MLEM) algorithm[3] was applied to reconstruct the 3D image. Results: With different boron concentration simulated in melanoma lesion, the detection efficiency of "True" events keeps stable. The reconstructed image matches well with the profile of the capture location scored in the patient geometry. The pass rate of gamma index analysis of 3 mm/3% for the relative distribution is about 90% with the prescribed dose level. Conclusion: This study shows that CC can be used to reconstruct the location of the capture reaction, which can be further used for the dose calculation in BNCT. LM-MLEM is an efficient algorithm to perform the reconstruction for this application. The results provide the fundamental basis for further clinical translation of the CC during BNCT.